2017
DOI: 10.21032/jhis.2017.42.4.309
|View full text |Cite
|
Sign up to set email alerts
|

Affected Model of Indoor Radon Concentrations Based on Lifestyle, Greenery Ratio, and Radon Levels in Groundwater

Abstract: Many people spend most of their day indoors, where low concentrations of radon (Rn-222) pose a significant environmental risk. Radon is a gas that decays from uranium (U-238). Its progeny can attach to aerosol and dust, and tends to get into the lungs [1]. In a previous study, 40% of all lung cancer deaths among miners were found to be related with radon progeny exposure. Indeed, 10% of all lung cancers may be caused by exposure to radon indoors: interestingly, these percentages were higher in never smokers th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Intergroup comparisons were conducted using t-tests for continuous variables and χ2-tests for categorical variables. We used multivariate conditional logistic regression to calculate odds ratios (OR) and 95% confidence intervals (CI) for lung cancer according to residential radon exposure (high vs. low), smoking status, and combinations of the two (low-radon dwelling non-smokers [reference], high-radon dwelling smokers, low-radon dwelling smokers, and high-radon dwelling smokers), after adjusting for second-hand smoking, sleeping hours, indoor hours, housing type, floor, presence of cracks, and green ratio [22]. All analyses were performed using SAS version 9.4 (SAS Institute Inc., Cary, NC, USA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intergroup comparisons were conducted using t-tests for continuous variables and χ2-tests for categorical variables. We used multivariate conditional logistic regression to calculate odds ratios (OR) and 95% confidence intervals (CI) for lung cancer according to residential radon exposure (high vs. low), smoking status, and combinations of the two (low-radon dwelling non-smokers [reference], high-radon dwelling smokers, low-radon dwelling smokers, and high-radon dwelling smokers), after adjusting for second-hand smoking, sleeping hours, indoor hours, housing type, floor, presence of cracks, and green ratio [22]. All analyses were performed using SAS version 9.4 (SAS Institute Inc., Cary, NC, USA).…”
Section: Discussionmentioning
confidence: 99%
“…Second-hand smoking was defined as living together with or working in proximity to a current smoker [20,21]. Green area corresponds to forest and grassland area; agricultural space, such as rice fields, is not included in green area [22].…”
Section: Smoking History and Covariablesmentioning
confidence: 99%
“…Using a structural equation model, Lee et al [8] showed that a high greenery ratio significantly increases indoor radon concentrations. The Environmental Geographic Information Service maintained by the Ministry of Environment in Korea provides access to greenery ratio data, which reflect the area of green area compared to administrative regions according to the city/county/district [9].…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, entrance concentration rates from soil and building materials are also affected by geographical characteristics and building design. Greenery ratio can be considered a factor connected to the exhalation rate of radon from surfaces [8]; cracks in the building and floors may also be factors. Therefore, we may consider the following statistical model for estimating entrance concentration rates from the soil and building materials for residence i:Si=β0+β1X1i+β2X2i+β3Y1i+β4Y2i+β5Y3i+ϵi, where Si = entrance concentration rates from soil and building materials for each residence i, X1i= greenery ratio of the administrative district to which residence i belongs, X2i= geometric mean of indoor radon levels of the administrative district to which residence i belongs, Y1i= type of building material of residence i, Y2i=…”
Section: Methodsmentioning
confidence: 99%